TNF-induced IL-8 and MCP-1 production in the eosinophilic cell line, EOL-1 - L. A. Goldstein; R. M. Strieter; H. L. Evanoff; S. L. Kunkel; N. W. Lukacs (Mediators of Inflammation)
The role of eosinophils in inflammation and their mode of activation is not well understood. Eosinophil accumulation and subsequent expression of cytokines at the site of inflammation may play a role in exacerbation of inflammatory responses. In the present study, we have examined the role of TNF-α in eosinophil activation and chemokine production using a human leukaemic eosinophil cell line, EOL-1. Initial studies demonstrated that TNF-α induced the upregulation of IL-8 and MCP-1 mRNA and protein. Kinetic studies indicated production of chemokines, IL-8 and MCP-1, as early as 4 h post-activation, with peak levels of chemokine produced at 8 h, and decreasing by 24 h post-TNF-α activation. When IL-10, a suppressive cytokine, was incubated with TNF-α and EOL-1 cells, no effect was observed on IL-8 and MCP-1 production. However, dexamethasone, a glucocorticoid, demonstrated potent inhibitory effects on the EOL-1-derived chemokines. These studies indicate that eosinophils may be a significant source of chemokines capable of participating in, and maintaining, leukocyte recruitment during inflammatory responses, such as asthma.